The impact of water conservation and reuse on the household economy - Buechler, Stephanie J.; Devi Mekala, G. (2003)
The urban, peri-urban and rural areas near Hyderabad city, located in Andhra Pradesh, south India are semi-arid and drought prone. In order to be able to engage in agricultural production, many farmers utilize wastewater for irrigation. Within these irrigated areas, many farmers pump groundwater for agricultural and domestic use. Five locations in the peri-urban and rural areas near Hyderabad were chosen to get a comprehensive view of groundwater use in wastewaterirrigated areas. This paper focuses on three aspects of the study: groundwater quality, farmer innovations that mitigate the harmful effects of wastewater and groundwater quality and the value of this agricultural production for the household economy. Wastewater use (or water reuse) for irrigation conserves fresh water resources in this and in many other areas of the world. In the area under study, wastewater use also causes groundwater recharge. However, 96% of domestic wastewater in Hyderabad receives little or no treatment and untreated industrial effluent is released with the wastewater into the wastewater-fed river, then into irrigation canals and storage tanks or ponds. Groundwater has become saline in all the wastewater-irrigated areas due to underground seepage, rendering it unsuitable for drinking and cooking purposes. With the rapid urban population growth and concurrent inter-basin transfers of water to meet urban water demand, wastewater volumes are increasing allowing more hectares of land to be brought under cultivation. With the expansion of wastewater-irrigated areas, groundwater levels in wastewater-irrigated areas have risen. As a result, additional land has also been brought under cultivation that is irrigated with groundwater. This generates income for more people and ensures their food security. However, groundwater pollution is also increasing. Many farming households have adapted their domestic and agricultural water use to the realities of deteriorating water quality yet greater water availability through the use of several innovative strategies.